Direct determination of kQ for Farmer-type ionization chambers in a clinical scanned carbon-ion beam using water calorimetry - Holm, Kim Marina; Jäkel, Oliver; Krauss, Achim (Physics in medicine and biology, 2022)
Within two studies, k Q factors for two Farmer-type ionization chambers have been experimentally determined by means of water calorimetry in the entrance channel (EC) of a monoenergetic carbon-ion beam (Osinga-Blättermann et al 2017 Phys. Med. Biol. 62 2033-54) and for a passively modulated spread-out Bragg peak (SOBP) (Holm et al 2021 Phys. Med. Biol. 66 145012). Both studies were performed at the Heidelberg Ion Beam Therapy Center (HIT) using the PTB portable water calorimeter but applying different initial beam energies of 429 MeV u−1 for the EC and 278 MeV u−1 for the SOBP as well as different scanning patterns of the irradiated field. Comparing their results revealed differences between the experimental k Q factors of up to 1.9% between the EC and the SOBP. To further investigate this unexpected difference, we performed additional k Q determinations for the EC of an 278 MeV u−1 monoenergetic carbon-ion beam and reevaluated the original data of Osinga-Blättermann et al (2017 Phys. Med. Biol. 62 2033-54). This new experimental data indicated no difference between the k Q factors for the EC and the SOBP and the reevaluation led to a substantial reduction of the originally published k Q factors for the EC of the 429 MeV u−1 beam (Osinga-Blättermann et al 2017 Phys. Med. Biol. 62 2033-54). Finally, no significant difference between the data for the EC and the data for the SOBP can be found within the standard measurement uncertainty of experimental k Q factors of 0.8%. The results presented here are intended to correct and replace the k Q data published by Osinga-Blättermann et al (2017 Phys. Med. Biol. 62 2033-54) and in Osinga-Blättermann and Krauss (2018 Phys. Med. Biol. 64 015009).